Supervised—not voluntary—upper limb exercise enhances vestibular function in Parkinson’s disease - Federica Ginanneschi; David Cioncoloni; Carla Battisti; Armando Bucciarelli; Federica Dominici; Roberto Marconi; Alessandro Rossi; Lucia Monti (Frontiers in Neurology)
BackgroundGait dysfunction has emerged as the greatest challenge in Parkinson disease (PD) management. Decreased vestibular efficacy may contribute to imbalance in PD. The present study aims to explore whether an upper limb aerobic exercise, performed using a device that primarily targets the axial muscles of the cervical-dorsal spine, can improve postural control and motor symptoms in PD.MethodsTwenty-eight patients with PD were evaluated before and after 2 months of exercise training, using dynamic posturography for the 6 conditions of the Sensory Integration Test (SOT) within the Equitest device, along with clinical measures. The effects of two exercise modes—supervised exercise (SE) and not supervised, voluntary exercise (VE)—were analyzed. Unified Parkinson Disease. Rating Scale (UPDRS) Part III and Hoehn and Yahr scale were used for clinical evaluation.ResultsA significant improvement in vestibular SOT values was observed only in subjects belonging to the SE group (55.6 ± 14.9 pre-training vs. 65 ± 11.2 post training, p = 0.017). Somatosensory and visual SOT scores did not change after training in any group. Both clinical scales showed statistically significant improvement after 8 weeks of training, but only in the SE group (p = 0.031) for the Hoehn and Yahr scale, and p = 0.007 for UPDRS Part III, indicating clinical improvement in the SE group.DiscussionActive assistive SE performed with upper limbs can improve the utilization of vestibular information, and, consequently, enhance motor performance in PD patients. It should therefore be considered a crucial treatment methodology for PD patients especially those with motor limitations in the lower limbs.